Effectiveness and implementation challenges of short-course all-oral BPaL and BPaLM regimens for drug-resistant tuberculosis: A systematic literature review - Fikria Adiputri; Rani Sauriasari; Dewi Danawati (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Drug-resistant tuberculosis (TB-RO), including MDR and XDR forms, remains a major global health burden due to prolonged, toxic, and often ineffective conventional regimens. The introduction of short-course all-oral therapies BPaL (bedaquiline, pretomanid, linezolid) and BPaLM (with moxifloxacin) has offered a promising alternative, with evidence of superior efficacy, safety, and patient adherence. However, implementation across countries continues to face challenges, including limited access to pretomanid, insufficient laboratory capacity, and scarce evidence for special populations. Purpose: To synthesize global evidence on the effectiveness, implementation challenges, and supporting factors associated with BPaL and BPaLM regimens for drug-resistant tuberculosis. Method: A Systematic Literature Review (SLR) following the PRISMA protocol was conducted to identify, screen, and include relevant studies published from 2016–2024. Data sources consisted of clinical trials, operational studies, cost-effectiveness analyses, bibliometric reviews, and qualitative stakeholder assessments. Thematic analysis was applied to summarize findings on treatment outcomes, adverse effects, operational barriers, and socio-economic influences that shape implementation across different health system contexts. Results: Regimens BPaL and BPaLM demonstrated high treatment success rates ranging from 84% to 97.6%, with rapid sputum culture conversion. Linezolid-related toxicities—such as neuropathy and myelosuppression—were common but manageable through dose adjustment and active monitoring. Cost-effectiveness analyses indicated up to a 25% reduction in per-patient expenditure compared with conventional regimens. Supporting factors included patient-centred care, psychosocial support, strengthened pharmacovigilance, and international technical collaboration. Key barriers comprised limited pretomanid access, inadequate laboratory capacity for drug-susceptibility testing, variable readiness of health systems, and limited evidence in special populations (children, pregnant women, and extrapulmonary TB cases). Conclusion: The global adoption of BPaL and BPaLM regimens marks a significant advancement in the treatment of drug-resistant tuberculosis by enabling shorter, safer, and more cost-effective therapy with consistently high treatment success and improved operational feasibility across diverse settings.